The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s003300101016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of limb veins

Abstract: Several imaging modalities are available for studying limb veins. Presently, the non-invasive duplex compression ultrasound and color Doppler imaging have replaced contrast venography as first-choice imaging modality in suspected deep vein thrombosis. This review discusses the current role of sonography and suggests a diagnostic strategy that minimises the need for contrast venography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The diagnostic criterion of fresh thrombosis was the presence of a constant intraluminal filling defect. 14 All the patients received an examination in both lower limbs 1 day before the planned surgery and on the third to fifth day after the operation.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic criterion of fresh thrombosis was the presence of a constant intraluminal filling defect. 14 All the patients received an examination in both lower limbs 1 day before the planned surgery and on the third to fifth day after the operation.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that females had high risk of DVT. 13 , 14 Increasing evidence suggests that women had higher platelet activity levels than men, 19 21 and estrogen likely plays a crucial role in the transcriptional regulation of coagulation protein genes. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic criterion for fresh thrombosis was the presence of a constant intraluminal filling defect. 14 The patients were examined before, after operation, and 1 month after surgery. All the patients underwent ultrasonography in both lower limbs 1 day before the planned surgery and on the third to the fifth day after operation, and 1 month after surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…The proposed diagnostic strategies combine the clinical probability score with D-dimer test and compression sonography. [64][65][66][67][68][69][70][71][72] The clinical risk assessment score is based on patient history, symptoms and physical examination. A history of malignancy, previous DVT, recent immobilization, recent surgery, and difference in calf diameter were the most useful criteria for assessing the clinical probability of DVT.…”
Section: Diagnostic Strategy For Symptomatic Patientsmentioning
confidence: 99%